Agricultural Vale Chain Finance for MSMEs and the Increasing Role of Fintech in Solving the Liquidity Constraints. Examples from Asia and Africa. - Nankya Ciatra; Sazir Nsubuga Mayanja (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2024)
Although challenges remain, efforts at innovations to support the provision of agricultural finance to smallholder farmers, especially through digital platforms, have demonstrated great potential and feasibility to increase access to liquidity by participants in the Agricultural Value Chain (AVC). Fintechs are the summary products of innovation in financial services delivery. In Asia, the Inclusive Financing for Agricultural Value Chains (IFS4Ag) project was aimed at deriving models for improving access to agricultural value chain finance (AVCF). According to the Digital Economy for Africa Initiative (DE4A) the continent should be digitally enabled by 2030. The research study is exploratory and mostly qualitative. Informal interviews have been given to stakeholders given that the majority of interviewees are micro and small farm holders. Otherwise, secondary sources have provided the bulk of information that informs the research. Findings are that governments, multilateral lending bodies, and affiliates have been variously and severally instrumental in piloting and actualizing improvement in financial service provision to the underprivileged by supporting delivery through fintech.